Multi-criteria optimization achieves superior normal tissue sparing in a planning study of intensity-modulated radiation therapy for RTOG 1308-eligible non-small cell lung cancer patients. Issue 3 (March 2016) - Kamran, Sophia C.; Mueller, Birgit S.; Paetzold, Peter; Dunlap, Joseph; Niemierko, Andrzej; Bortfeld, Thomas; Willers, Henning; Craft, David
Abstract: Purpose: In this planning study, we studied the benefit of intensity-modulated radiation therapy (IMRT) with multi-criteria optimization (MCO) in locally advanced non-small cell lung carcinoma (NSCLC). Methods: We selected 10 consecutive patients with gross tumor within 1 cm of the esophagus eligible for RTOG 1308, randomized phase II trial of 70 Gy protons vs photons. Planning was performed per protocol. In addition, a novel approach for esophagus sparing was applied by making the contralateral esophagus (CE) an avoidance structure. MCO and non-MCO plans underwent double-blinded review. Plan differences in dose–volume histogram parameters were analyzed. Results: Median plan differences were mean lung dose = 0.8 Gy ( p = 0.01), lung V20 = 1.1% ( p = 0.06), heart V30 = 1.0% ( p = 0.03), heart V45 = 0.6% ( p = 0.03), esophagus V60 = 1.2% ( p = 0.04), and CE V45 = 3.2% ( p = 0.01), all favoring MCO over non-MCO. PTV coverage with 95% dose was ⩾98.0% for both plans. There were 5 minor protocol deviations with non-MCO plans and 2 with MCO. Median improvement of active planning time with MCO was 88 min ( p < 0.01). Physicians preferred 8 MCO and 2 non-MCO plans ( p = 0.04). Conclusions: MCO plans yielded significant improvements in organ-at-risk sparing without compromising target coverage, consumed less dosimetrist time, and were preferred by physicians. We suggest incorporating MCO into prospective clinical trials.